Cost Efficiency of UK commercial banks — A Stochastic Frontier Analysis - Xing, Lingzi (2019)
This research analyses the cost efficiency of the UK commercial banks by using stochastic frontier analysis (SFA). The main objective is to estimate the cost efficiency of the UK banking industry by employing the most recent data from 2011 to 2018. On average, the cost efficiency score ranges from 79.89% to 87.54%, showing an upward trend over time. The single-stage regression model is adopted to measure the impacts of macroeconomic variables on cost efficiency. The results indicate the gross domestic product (GDP) growth rate, inflation rate and unemployment rate are negatively correlated with the cost efficiency of UK banks, whereas the real interest rate has a positive impact on the level of cost efficiency. Keywords: cost efficiency, stochastic frontier analysis, UK banks;